Techno-economic pre-feasibility study of wind and solar electricity generating systems for households in Central Finland - Alavi, Seyed Mehdi (2014)
The objective of this work is to investigate the viability of a wind, PV or hybrid wind-PV system supplemented with battery storage for electricity production to meet the electricity consumption of a typical household apartment in Central Finland. The assessment criteria for the analysis were cost of energy and total net present cost of each system configuration. We selected the Hybrid Optimization Model for Electric Renewables (HOMER) software, RETScreen, and PVsyst in our analysis and finally only HOMER was considered for performing system optimization analysis because of the creditability of its results. A PV-battery system is recognized as the most economically feasible option in our site with the lowest cost of energy as well as net present cost, however its application results in utilization of significant number of batteries which is not efficient. On the contrary, due to low wind speed in the site, the use of wind-battery power system comes out to be the most expensive option. The hybrid wind-PV-battery system is more preferable for its ability to diversify energy sources, and thus to increase reliability of the system and likely system performance, although it is more costly than the PV-battery system. For these reasons, the hybrid wind-PV battery system was recommended for supplying the electrical load requirement of our study.